Community Based Ecotourism Management in Xieng Lom village, Luang Prabang Province, Lao PDR - Duangvilaykeo, Thipphavanh; Lattanasouvannapon, Champa; Phosikham, Thongmala (Souphanouvong University Journal Multidisciplinary Research and Development, 2015)
Community based ecotourism management in Xieng Lom village, Luang Prabang province is a study of the following: to investigate the management of community based ecotourism in Xieng Lom village, to study the level of participation by local people in community based ecotourism management and also the management approach towards sustainable community based ecotourism. This study employs both quantitative and qualitative analysis methods. Population and sampling: 65 people: 30 people from the tourism sectors (public and private sectors): 35 from the villager. Material used in data collection was questionnaire surveys and face-to-face interviews. The study used descriptive analysis and analysis questionnaires from Statistical Package for Social Sciences (SPSS). This information was presented through frequency, mean and percentage graphs. The information collected from interviewswas examined in regard tothe relevant theories and methodology consistent with the purposes of the study in order to present the results of estimation. Results from the study indicated that Xieng Lom village is an important ecotourism model that can offer a variety of beautiful landscape and scenery, in particular, mountains, rivers and forests. There is also a range of ecotourism activities, for example, riding elephants through the village to observe the village’s way of life, visiting villages and farming sites, and trekking to the mountains and visiting waterfalls. Rafting and kayaking are also well known adventure tourism activities. Currently, most ecotourism activities are operated and run by tour companies and resorts, especially, trekking, riding elephants, and kayaking down the Khan River. These tour packages are now available for those who prefer adventure tourism. The level of overall participation of villagers in the community based ecotourism management project in Xieng Lom village was on “neutral” level with a total mean of 2.97: The level of participation in planning of the villagers who sometimes participate, has a mean of 2.73. The level of participation in the implementation of those who sometimes participate, has a mean of 3.32. The level of participation in obtaining benefits from tourism development shows those villagers who sometimes participate, has a mean of 3.01. The level of participation in evaluation shows the villagers who sometimes participate has a mean of 2.84. All stakeholders, the Department of Information, Culture and Tourism, the NGOs, tourism enterprises, people involved from villages are important parts and components of sustainable community based ecotourism development and mangement in Xieng Lom village, Luang Prabang city and province. These people have played important roles in ecotourism activity development. Another important thing is to educate local people , both male and female about sustainable development.The villagers are proud of what they have done to protect their own future resources and realize the impacts of environmental issues and the need to find solutions. Development processes and real implementation would help people fully understand the needs and regulations of community based ecotourism in the long term.